Stability Indicating Reversed-phase High-Performance Liquid Chromatography Method Development and Validation for Simultaneous Estimation of Bismuth Subcitrate, Tetracycline, and Metronidazole in Bulk and Capsule Dosage Form - Prathap, Dr. B. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of the study was to develop a new, simple, sensitive, precise, accurate, and stability indicating reversedphase high-performance liquid chromatography (RP-HPLC) method for the simultaneous estimation of bismuth subcitrate, tetracycline, and metronidazole in the combined capsule dosage form. Materials and Methods: The analysis with Inertsil C18 (250 × 4.6 mm, 5 μ) column under ambient temperature and using mobile phase phosphate buffer pH = 3.5 and methanol in the ratio of 40:60 v/v. Results and Discussion: The retention time of metronidazole, tetracycline, and bismuth subcitrate was found to be 2.599 min, 3.805 min, and 4.661 min, respectively. The proposed method was validated according to the ICH guidelines. The linearity study of metronidazole, tetracycline, and bismuth subcitrate was found to be 125–625 μg/ml, 125–625 μg/ml, and 140–700 μg/ml and correlation coefficient (r2) was found to be 0.9994, 0.9993, and 0.9993, respectively. The percentage recovery was obtained as 99.95%, 99.86%, and 100.27% metronidazole, tetracycline, and bismuth subcitrate, respectively. The studies were carried out by conducting deliberate degradation of the sample with exposure to stress conditions such as acidic, alkaline, thermal, oxidizing agent, and light. Conclusion: This method was validated and meets the regulatory requirements for specificity, linearity, limit of detection, limit of quantification, precision, accuracy and stability for the determination of metronidazole, tetracycline, and bismuth subcitrate in bulk and capsule dosage form by RP-HPLC.